Molecular characterization of Brucella abortus from cattle and buffaloes - JAIN, ANKIT; SHARMA, N S; NARANG, DEEPTI; CHANDRA, MUDIT; KAUR, PAVITER; ARORA, A K (The Indian Journal of Animal Sciences, 2014)
Out of 84 samples collected from cattle and buffaloes with history of abortions and reproductive disorders 9 (10.71%) were positive by isolation and 12 (14.28%) were positive by PCR. The amplicons of 905bp and 223bp were amplified using genus specific F4/R2 and B4/B5 primers, respectively. Primers F4/R2 and B4/B5 are sensitive and specific to detect Brucella 16S rRNA and bcsp31gene. Prevalence of Brucella abortus was 14.54% in buffaloes and 13.79% in cattle respectively by PCR. Polymerase chain reaction proved to be a better technique with regards to sensitivity, specificity, safety, rapidity of analysis and easy of automation for detection of Brucella species in comparison to conventional methods. bcsp31 and 16S rRNA are conserved genes and may be good candidate for diagnosis of Brucella species.